Evaluasi Rasio Likuiditas dan Profitabilitas sebagai Indikator Kinerja Keuangan: Studi Kasus PT Mayora Indah Tbk di BEI 2022–2024 - Aulia Maria Ulfah; Hari Padly; Abdillah Abdillah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to assess the financial performance of PT Mayora Indah Tbk. through an analysis of profitability and liquidity ratios over the past five years. A company's financial performance is a key indicator in evaluating operational success, managerial efficiency, and overall financial health. This assessment is important for investors, management, and other stakeholders in strategic decision-making. This study uses a quantitative descriptive approach with a case study as its primary method. The data analyzed are secondary data in the form of PT Mayora Indah Tbk.'s annual financial reports published on the Indonesia Stock Exchange. The ratios analyzed include Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) as profitability indicators, and Current Ratio (CR), Quick Ratio (QR), and Cash Ratio as liquidity indicators. The results of the study indicate that in general, the company is able to maintain a stable level of profitability, despite minor fluctuations from year to year. ROA and ROE indicate that management is quite effective in managing assets and equity to generate profits. NPM also shows a competitive net profit margin compared to similar industries. Meanwhile, the liquidity ratio indicates that PT Mayora Indah Tbk. has a strong and consistent ability to meet its short-term obligations. The CR, QR, and Cash Ratio are all within safe limits, indicating healthy liquidity. In conclusion, PT Mayora Indah Tbk. demonstrates good financial performance in terms of both profitability and liquidity, making it a company worthy of consideration for long-term investment.